(3GdhGaj HMd GdcGaj aj Ydej GdYQhV hGdbhGajs - (3YHO GdQMef Hf YjSi Hf eQTO GdYeQjs; (3TgGH GdOjf CHh GdYHGS CMeO Hf YHGO Hf TYjH GdUCHj GdbGgQj GdTGaYj, GdNhGU,J (B858 (3g` s
(3ChdgG (B:s
(3Gddge jG cGaj GdegeGJ jhe GdaUd hGdejRGf jGhGaj GdYWjI ef hGaQ GdaVd hcGed GdEMSGf s
(3BNQgG (B:s
(3hjMTQfG aj ReQI fHjg GdcGed hGdMeOddg Ydi fYeI GdJeGe hefg GdJhajb aj GdeHOC hGdNJGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais